2020
DOI: 10.1093/mnras/staa928
|View full text |Cite
|
Sign up to set email alerts
|

NGTS J214358.5−380102 – NGTS discovery of the most eccentric known eclipsing M-dwarf binary system

Abstract: We present the discovery of NGTS J214358.5-380102, an eccentric M-dwarf binary discovered by the Next Generation Transit Survey. The system period of 7.618 days is greater than many known eclipsing M-dwarf binary systems. Its orbital eccentricity of 0.323 +0.0014 −0.0037 , is large relative to the period and semi-major axis of the binary. Global modelling of photometry and radial velocities indicate stellar masses of M A =0.426 +0.0056 −0.0049 M , M B =0.455 +0.0058 −0.0052 M and stellar radii R A =0.461 +0.03… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Miller et al [273] used TESS data to characterise 2MASS J06464003+0109157, an EB consisting of two 0.6 M stars. Acton et al [274,275] studied NGTS J214358.5−380102, an M-dwarf EB with an unusually large period (7.62 d) and eccentricity (0.323), and NGTS J0930−18, an EB containing a 0.58 M and a 0.08 M star. Swayne et al [276] used the TESS data of 1SWASP J011351.29+314909.7 (Figure 7) to rule out a previous suggestion that the M-dwarf secondary component was unexpectedly hot.…”
Section: Standard Ebsmentioning
confidence: 99%
“…Miller et al [273] used TESS data to characterise 2MASS J06464003+0109157, an EB consisting of two 0.6 M stars. Acton et al [274,275] studied NGTS J214358.5−380102, an M-dwarf EB with an unusually large period (7.62 d) and eccentricity (0.323), and NGTS J0930−18, an EB containing a 0.58 M and a 0.08 M star. Swayne et al [276] used the TESS data of 1SWASP J011351.29+314909.7 (Figure 7) to rule out a previous suggestion that the M-dwarf secondary component was unexpectedly hot.…”
Section: Standard Ebsmentioning
confidence: 99%
“…Miller et al [273] used TESS data to characterise 2MASS J06464003+0109157, an EB consisting of two 0.6 M stars. Acton et al [274,275] studied NGTS J214358.5−380102, an M-dwarf EB with an unusually large period (7.62 d) and eccentricity (0.323), and NGTS J0930−18, an EB containing a 0.58 M and a 0.08 M star. Swayne et al [276] used the TESS data of 1SWASP J011351.29+314909.7 (Fig.…”
Section: Standard Ebsmentioning
confidence: 99%
“…NGTS-4b, a sub-Neptune-sized planet in the 'Neptunian Desert' (West et al 2019). The enormous amount of data collected by the survey has led to many other interesting discoveries, including the most massive planet orbiting an M-type star NGTS-1b (Bayliss et al 2018); an ultrashort-period brown dwarf transiting a tidally locked and active M dwarf (Jackman et al 2019); the most eccentric eclipsing M-dwarf binary system found to date (Acton et al 2020a); a transiting 'warm Saturn' recovered from a TESS single-transit event (Gill et al 2020); and transit timing variations on the ∼540-d-period exoplanet, HIP 41378 f (Bryant et al 2021). NGTS operations include a survey of nearby open clusters and star forming regions (see Gillen et al 2020b for Paper I andJackman et al 2020 for Paper II), within which the subject of this paper was detected.…”
Section: Introductionmentioning
confidence: 99%